PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT DESA KAYU ARA DI KECAMATAN MENYUKE KABUPATEN LANDAK - Ferdy, Rikki; Usman, Fadilah H; Sisillia, Lolyta (JURNAL HUTAN LESTARI, 2017)
Plants that have medicinal properties are often used by people around the forest to cope with various diseases they suffer. Plants are easy to find and easy to process and economical. This research aims to reveal the types of medicinal plants and their use by the community in Desa Kayu Ara in Menyuke Subdistrict of Landak Regency. This research uses snowball sampling technique or done in a series by requesting information from people that became samples. The research data showed the use of medicinal plants included plant species, family, the part used, the types of treatable disease, the way of processing, the form of concoction, the use and the dose. The results showed that the medicinal plants used are as many as 44 species of 32 families, and if grouped by habitus, the most widely used herbs used as medicine are as many as 17 species (38.63%). Based on the part used, it turns out that the leaves are widely used as many as 22 species (50%), and the way of processing is mostly boiled with as many as 22 species (50%). Based on the use, the most widely used method is by drinking with as many as 20 species (45.45%), and the method of medicinal use is mostly to treat the internal disease with as many as 37 species (84.09%). While based on the form of herb, 100% is used as single herb.Keywords: Community of Kayu Ara Village, Utilization of Medicinal Plants.